Plant functional groups mediate drought resistance and recovery in a multisite grassland experiment. (5th December 2018) - Mackie, Kathleen A.; Zeiter, Michaela; Bloor, Juliette M. G.; Stampfli, Andreas
Abstract: Climate change predictions suggest that summer droughts will become more intense and recurrent in Europe. While drought‐induced reductions in grassland primary productivity are well documented, the drivers behind drought resistance (the capacity to withstand change) and recovery (the capacity for recovery of function) of above‐ and below‐ground biomass remain poorly understood. Across eight grasslands differing in plant community productivity (CP), we investigated the effects of summer drought on plant and soil microbial variables, plant nutrient content, and soil nitrogen (N) availability. We examined the linkages between CP, soil N, drought responses of plant and microbial communities, and relative drought responses of plant and microbial biomass. Plant and microbial variables were recorded at the end of a 3‐month rainfall exclusion period. Plant variables were also assessed during a 10‐month drought recovery period. Experimental drought decreased plant biomass and increased plant C:N ratios, but had no effect on total microbial biomass across sites. Instead, drought caused shifts in plant and microbial community structures as well as an increase in arbuscular mycorrhiza fungi biomass. Overall, plant biomass drought resistance was unrelated to CP or microbial community structure but was positively related to drought resistance of forbs. In the month after rewetting, soil N availability increased in droughted plots across sites. Two months post‐rewetting, droughted plots had higher plant N concentration, but lower plant N use efficiency. The short‐term drought recovery of plant biomass was unrelated to CP or soil N availability, but positively related to the response of grass biomass, reflecting incomplete recovery at high CP. Ten months after rewetting, drought effects on plant biomass and plant N content were no longer apparent. Synthesis. Our results suggest that drought resistance and recovery are more sensitive to plant community composition than to community productivity. Short‐term recovery of plant biomass may also benefit from increased soil N availability after drought and from a high abundance of soil fungi in low productivity sites. Our findings underline the importance of plant functional groups for the stability of permanent grasslands in a changing climate with more frequent drought. Abstract : Our results suggest that drought resistance and recovery are more sensitive to plant community composition than to community productivity. Short‐term recovery of plant biomass may also benefit from increased soil N availability after drought and from a high abundance of soil fungi in low productivity sites. Our findings underline the importance of plant functional groups for the stability of permanent grasslands in a changing climate with more frequent drought.